NGUYEN DU’S PERCEPTION ABOUT CHINA UNDER THE QING DYNASTY THROUGH BAC HANH TAP LUC - Lê Quang Trường (Tạp chí Khoa học Đại học Đà Lạt)
Nguyen Du (1765-1820), with courtesy name To Nhu, poetic name Thanh Hien, and other pseudonym Hong Son Liep Ho, was born into the noble Nguyen clan of Tien Dien village in central Vietnam. Many of his family members served in high positions in the imperial mandarin system of the Le-Trinh dynasty. Inheriting honors from his father, Nguyen Du was bestowed the titles: Hoang Tin Great Man, Guard Commandant of Origin, and Thu Nhac Count. Therefore, deep within his conscience, Nguyen Du always felt indebted to the Le dynasty. However, the rapid replacement of the Le-Trinh by the Tay Son and then by the Nguyen dynasty during the chaotic years of the eighteen century seriously challenged his beliefs and emotions, pushing him into a reclusive lifestyle during his reluctant service to the Nguyen dynasty. In the 12th year of Gia Long (1813), Nguyen Du was appointed the mission leader on a yearly tribute trip to China, during which he wrote a collection of poetry titled “Bac hanh tap luc” (Trivial Notes on the Northward Trip). His “trivial notes” revealed his complicated thinking and feelings about the Chinese landscape, people and culture under the rule of the Jiaqing emperor. This article analyzes Nguyen Du’s rational and emotional perceptions of China, especially Chinese culture as implied in “Bac hanh tap luc”, to better understand a case of direct interaction of a Vietnamese Confucian scholar with imperial China.